Minimum guidelines for CSV implementation - Bui Le Vinh; Vu Thanh Bien; Do Thi Thu Ha; Nguyen Tuan Cuong; Trieu Hong Lua; Talsma, Tiffany; Spillane, Charles; Brychkova, Galina; McKeown, Peter (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate-smart village (CSV) has been demonstrated as a good model to practice climate-smart agriculture technologies and practices (CSA T&Ps) for enhancing adaptive capacity and resilience to climate change in rural areas worldwide. This material documents detailed stepwise guidelines for CSV implementation at village level from three CSVs that have been successfully established for three distinctive agroecologies of Yen Bai province. These CSVs were developed in three different projects, such as the CCAFS FP2.1 (2015-2018), VIBE 2018.05 (2019-2021), and NTM (2020) projects. The document will provide technical guidance for improving the implementation of Vietnam’s National Target Program on New Rural Development (NTM) in the 2021-2030 Strategy towards climate adaptation and resilience in vulnerable rural areas.